Community breeding of livestock pays off in Ethiopia - Okeyo Mwai, Ally (International Livestock Research Institute, 2011)
On 15 and 16 November 2011, the International Livestock Research Institute (ILRI), the Ethiopian Institute of Agricultural Research (EIAR) and the Swedish University of Agricultural Sciences (SLU) held a workshop on Sharing Research Results on Trypanotolerance in Indigenous Cattle Breeds and Experiences of Community Based Breed Improvement of Indigenous Sheep in Ethiopia. Here Okeyo Mwai from ILRI explains the importance of community breeding programs.